Dental Students’ Perceptions on Restorative Dentistry Education in Shahid Beheshti Dental School - Najafi, Ahmad; Jaberi Ansari, Zahra; Naseri, Mohammad (Journal of Dental School, 2019)
Objective: Numerous studies have emphasized on the importance of developing an ideal educational system for high-quality dental education. The present study sought to assess the perception of dental students on operative dentistry education in Department of Restorative Dentistry, Shahid Beheshti Dental School, Tehran, Iran. Methods: In this descriptive cross-sectional study, 220 students were selected and given a questionnaire including demographic , grades in operative dentistry clinical and didactic courses, the efficacy of preclinical courses in preparing students for clinical practice, ways to improve competency and expertise of students for clinical setting, student’s opinion on relating the assessment tests with the taught topics, required instructional resources for assessment of students’ proficiency in restorative dentistry and satisfaction rate of students with clinical courses offered in the current curriculum. Data were analyzed using descriptive statistics (SPSS 18). Results: The Clinical Operative Dentistry 3 and Preclinical Dental Anatomy received a mean satisfaction score of 3.31 and 2.74, respectively. Furthermore, 57.3% of students highly emphasized the necessity of studying textbooks of restorative dentistry. 50.5% of students believe that lectures by instructors along with active participation of students were the best method for didactic operative dentistry courses. In addition, 60.5% were in favor of using a combination of textbooks, lectures, and class notes for the assessment of students’ learning. Conclusion: The present study revealed that Department of Restorative Dentistry in Shahid Beheshti Dental School is successful in its teaching and achieving students’ satisfaction. However, some revisions need to be made in educational methods and contents and active participation of students in class discussions should be encouraged as well.